The moderating effect of leadership between organizational structure, organizational culture, rewards, external consultants on organizational performance in Jordanian government department - Ahmad, Hodifa Farhan (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis, 2019)
The scope of this study focuses only on strategy execution level including (organizational structure, organizational culture, rewards system an external consultant) issues and their effect on organizational performance moderating through the leadership among public organizations in Jordan. Thus, the study excludes other issues or factors which may occur in the process. Undoubtedly, contributions from other issues or factors may provide important information on strategic planning process as well. If such situation exists, it is then considered as a limitation of the study.